Influence of the pectin and cellulose on the performance of cross-flow microfiltration - Heidy Lorena Gallego-Ocampo; Karen Johana Ortega-Villalba; Carlos Antonio Vélez-Pasos; Ronald Joanny Rojas-Alvarado (Revista Facultad de Ingeniería Universidad de Antioquia, 2022)
The cross-flow microfiltration (CFM) of fruit juices allows obtaining products of high quality by conserving their organoleptic characteristics and microbiological stability during storage. The effect of the main macro-compounds and the transmembrane pressure (TMP) on the process performance with model fluids was evaluated. The model fluids concentration varied between 0.25 and 0.75% for pectin and 0.04 and 0.08% for cellulose. To study the influence of transmembrane pressure (TMP) and concentration on the hydrodynamic properties of the fouling layer ( , diffusivity (D) and the boundary layer thickness ) the Box-Behnken design with three replicas in the center was used. It was found that the CFM process is efficient and commercially feasible when working at a constant TMP of 1.93 bar and at concentrations of pectin and cellulose of 0.25% and 0.0513%, respectively.